Psychometric properties of the Suicidal Ideation Attributes Scale (SIDAS) in assessing suicidal ideation in adolescents - Alison L. Calear; Aliza Werner-Seidler; Helen Christensen; Bridianne O’Dea; Kate Maston; Michelle Torok; Philip J. Batterham (Child and Adolescent Psychiatry and Mental Health, 2026)
Abstract Background The paucity of valid and reliable tools for assessing the severity of suicidal ideation in adolescents is an impediment to youth suicide prevention efforts. This study aimed to examine the psychometric properties of the Suicidal Ideation Attributes Scale (SIDAS), a brief scale of suicidal ideation, in a large community-based sample of adolescents. Methods Data for the current study was drawn from the baseline, 6–week, and 12–month follow–up surveys from the Future Proofing study, a prospective cohort study of adolescent mental health and wellbeing. This study includes 5885 adolescents (48% female, 48% male, 4% other gender) aged between 11 and 17 years. Results A confirmatory factor analysis supports that the SIDAS has an excellent fit to a single–factor model, very good internal consistency (α = 0.90), and strong test–retest reliability ( r = 0.69), despite suicidal ideation being prone to marked temporal fluctuation. Construct validity was demonstrated through positive correlations with depressive symptoms ( r = 0.59), psychological distress ( r = 0.53), and negative correlations with wellbeing ( r = − 0.36). Predictive validity analysis showed a cut-point of ≥ 1 is indicative of an increased risk of suicide attempt among adolescents at 12 months follow-up. Although gender diverse adolescents showed higher and more variable scores relative to males and females, there was no compelling evidence that sociodemographic factors significantly influenced response patterns. Conclusions Given its strong psychometric properties, the SIDAS has future clinical and research utility for the screening of suicidal ideation and suicide risk in adolescents.